Kinerja Keuangan Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia dengan Metode Economic Value Added (EVA) - Rofinus Leki; Firda Nosita (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2019)
The aim of this study is to analyze the performance of cigarette companies listed on the Indonesia Stock Exchange by using Economic value added (EVA) technique. The data was collected from financial report of four cigarette companies for 2014 to 2018 period. The result shows that three of four cigarette companies, namely PT. Gudang Garam, Tbk, PT. HM Sampoerna, Tbk, and PT. Wismilak Inti Makmur, Tbk has positive EVA respectively. While, PT. Bentoel Internasional Investama, Tbk has poor performance by producing negative EVA. The result indicate that three out of four companies able create value for shareholders. EVA for cigarette companies are depend on company’s ability to create profit amid tax, excise and other regulatory conditions that greatly impact the performance of cigarette companies. The good investment and financing decisions become an integral part and encourage the companies value creation.